PERANCANGAN VISUAL IDENTITY ALE-ALE “PAK IN” KHAS KOTA SAWAHLUNTO - PITRIA DIYAH LUSIANI, Dr. Budiwiran, M.Pd., Hendra Afriwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The not yet optimal visual identity of Ale-Ale Pak In's business is based on observations of the current conditions, so it has not shown a visual identity that can be recognized by the public or consumers. Besides the competitors of the Ale-Ale business that developed in Sawahlunto itself. The purpose of this design is to create a brand in the form of logogram and logotype information.The design method used is the Glass Box method, the design carried out rationally and logically, starting from data collection, interviews and observations.The analytical approach used is the 5W + 1H analysis method (what, who, where, when, why, how) to find a solution to the problem at hand.The design of the main visual media identity ale-ale Pak In is the manual book as the main media, as well as supporting media namely, sign board, business cards, letters, envelopes, packaging, invoices, clothes, aprons, posters, x-banners, paper bags, mugs , stickers, pins and stamps, which aim to strengthen the application of the main media.Keywords: Designing Visual Identity, Brands, and Ale-Ale Pak In.